Pharmacy employees' self-rated knowledge, use and attitudes toward homeopathy: A comparative survey in Sweden and Germany - Essling E.; Khalaf A. (Sciendo, 2019)
Background: Homeopathy is being increasingly practiced within different medical areas of use. Homeopathic medicines are sold in German pharmacies, whereas the assortment of Swedish pharmacies does not include homeopathic medicines. Despite differences between Sweden and Germany, homeopathic medicines are classified as drugs in both countries.